2016
DOI: 10.21037/gs.2016.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Is vascular flow a predictor of malignant thyroid nodules? A meta-analysis

Abstract: Background: Several reports have proposed that increased vascular flow on color Doppler sonography may be associated with malignancy in thyroid nodules. Others have described no correlation between the presence of flow and risk of malignancy. The purpose of this study was to determine whether the vascularity of a thyroid nodule can aid in the prediction of malignancy by performing a meta-analysis of the current literature.Methods: Independent reviewers conducted a systematic review of publications from PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…We did not find any significance between central vascularization of the nodules and malignant outcome, a result in concordance with a meta-analysis performed on 5 studies including 540 nodules, which indicated that there was no significant difference in internal vascularity (95% CI: -72.067, 2.824) between malignant and benign thyroid nodules. 24 We did not evaluate margins and taller than wide shape, since these parameters were not always available in the US reports included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any significance between central vascularization of the nodules and malignant outcome, a result in concordance with a meta-analysis performed on 5 studies including 540 nodules, which indicated that there was no significant difference in internal vascularity (95% CI: -72.067, 2.824) between malignant and benign thyroid nodules. 24 We did not evaluate margins and taller than wide shape, since these parameters were not always available in the US reports included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis including a total of 1,048 nodules with available data about color Doppler signs showed that nodules with intranodular blood flow are 4 times more likely of being cancers than nodules without intranodular blood flow [16]. However, Khadra et al [17] showed in another recent meta-analysis that an enhanced vascularization on Doppler sonography is not predictive of malignancy in all nodules, but may help in the risk stratification of nodules with suspicious US features. On the contrary, we found that information about vascularity specifically in nodules with high-suspicion US features (TR4 and TR5) significantly reduced the ROC-AUC of ACR TI-RADS for the identification of malignant nodules, due to a significant reduction of its sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…24,31,32 Some studies have claimed that hypervascularity is an independent predictor of thyroid cancer. 14,33 Khadra et al 34 reported that hypervascularity may indicate a high risk of thyroid malignancy when combined with suspicious GSU features in thyroid nodules with indeterminate cytology. However, they also claimed that hypervascularity itself was not an independent predictor of thyroid malignancy.…”
Section: Doppler Ultrasoundmentioning
confidence: 99%
“…However, they also claimed that hypervascularity itself was not an independent predictor of thyroid malignancy. 34 Some studies have suggested that central vascularity is a feature for thyroid malignancy, whereas benign thyroid nodules tend to have peripheral vascularity ( Figure 12). 23,[35][36][37][38] However, other studies have noticed a higher association of central vascularity with benignity rather than malignant status of thyroid nodules.…”
Section: Doppler Ultrasoundmentioning
confidence: 99%